Optimization of home treatment in haemophilia: effects of transmural support by a haemophilia nurse on adherence and quality of life. (25th October 2016) - Lock, J.; Raat, H.; Peters, M.; Scholten, M.; Beijlevelt, M.; Oostenbrink, R.; Leebeek, F.W.G.; Moll, H.A.; Cnossen, M.H.
Abstract : Background: Transmural support by a haemophilia nurse may improve treatment and may empower parents and patients. Aim: To measure the effect of structured home visits by a haemophilia nurse in (parents of) patient on aspects of prophylactic home treatment. Methods: A multicentre intervention study in two paediatric haemophilia treatment centres was performed. Primary outcome measures were: adherence to prescribed treatment, health‐related quality of life and behavioural scores. Secondary outcome measures were: total clotting factor consumption, self‐efficacy and number of joint bleeds. Results: Over a period of 22 months (median, IQR 21–23), four to seven home visits in 46 patients (mean age 9.4 ± 4.2 years) were made. No difference in adherence to prescribed treatment was seen after the home visits when compared to baseline measurements. Both the Child Health Questionnaire (CHQ) scales on 'Role functioning – Emotional/Behavioural' ( P = 0.02, d = 0.53) and 'Parental Time Impact' ( P = 0.04, d = 0.33) were reduced after intervention. The disease‐specific Haemo‐QoL questionnaire showed improvement in domains: 'Family' ( P = 0.04, d = −0.14), 'Friends' ( P = 0.03, d = −0.29) and 'Perceived support' ( P = 0.03, d = −0.37). Significant improvement was observed with regard to domain 'Communication' of the VERITAS‐Pro scale ( P = 0.03, d = −0.28). Conclusions: After a period of transmural care by a haemophilia nurse, significant but small positive effects were demonstrated with regard to communication and increase of perceived support between parents and haemophilia treatment centre. No improvement was observed in other outcome measures.